Ecologically Sustainable Development (ESD) Useful Australian Land Use Practice-Suitable for the World - Alam, Sheikh Mahabub (Edelweiss Applied Science and Technology, 2019)
Protection of the Environment and Sustainability goes hand in hand as one mechanism compliments the other. On the other hand, Sustainable Economic Growth can only be achieved if it is linked to Ecologically Sustainable Development (ESD). Sustainability can best be described as "Living within the limit of what the environment can provide while safe guarding the environment for future generation, Understanding the many connections between environment, society and economy, and equitable distribution of resources and opportunities". Uncontrolled Green House Gas Emission has caused global warming, sea level rise, change of weather pattern (e.g severe untimely rainfall at unusual location), and alarming increase of natural disasters (Cyclone, Hurricane, Floods, Tsunamis and other natural phenomena). Third world countries are worst affected by the Green House Gas Emission and Global Warming Impact and Bangladesh is one of them. UN has taken a leading role and guiding the world to work together not only to reduce pollution but to make significant contribution in achieving pristine environmental conditions. Under the umbrella of UN, the world is now taking collective action to reduce Green House Gas Emission and Tackle Global Warming Impacts. Concerted efforts must be taken in an accelerated pace to educate at Global, Regional, National and Community level, about the benefits of the above-mentioned concepts and introduce incentive-based programs for mass participation. The environmental cleanup process should start from individual home and gradually extending to community, national and global level to achieve accelerated measurable success. An opportunity must be created to reform land use change, replacing pollution producing industries with environmentally sustainable practices. It is overdue to put through a series of EPA recommended processes to clean up the contaminated land, soil and water and secondly, introduce and adapt an Ecologically Sustainable Development program. The long-term goal should be to expedite and spread the land use change practices to relace the contaminated practices and introduce mandatory adaption of environment friendly technology for the ongoing industrial and business activities to reduce pollution while contributing improving the environment. With a global collective action this world can be transformed into a heaven on earth.